A novel membrane complex is required for docking and regulated exocytosis of lysosome-related organelles in Tetrahymena thermophila - Kuppannan, Aarthi; Jiang, Yu-Yang; Maier, Wolfgang; Liu, Chang; Lang, Charles F; Cheng, Chao-Yin; Field, Mark C; Zhao, Minglei; Zoltner, Martin; Turkewitz, Aaron P (PLoS genetics, 2022)
In the ciliate Tetrahymena thermophila, lysosome-related organelles called mucocysts accumulate at the cell periphery where they secrete their contents in response to extracellular events, a phenomenon called regulated exocytosis. The molecular bases underlying regulated exocytosis have been extensively described in animals but it is not clear whether similar mechanisms exist in ciliates or their sister lineage, the Apicomplexan parasites, which together belong to the ecologically and medically important superphylum Alveolata. Beginning with a T. thermophila mutant in mucocyst exocytosis, we used a forward genetic approach to uncover MDL1 (Mucocyst Discharge with a LamG domain), a novel gene that is essential for regulated exocytosis of mucocysts. Mdl1p is a 40 kDa membrane glycoprotein that localizes to mucocysts, and specifically to a tip domain that contacts the plasma membrane when the mucocyst is docked. This sub-localization of Mdl1p, which occurs prior to docking, underscores a functional asymmetry in mucocysts that is strikingly similar to that of highly polarized secretory organelles in other Alveolates. A mis-sense mutation in the LamG domain results in mucocysts that dock but only undergo inefficient exocytosis. In contrast, complete knockout of MDL1 largely prevents mucocyst docking itself. Mdl1p is physically associated with 9 other proteins, all of them novel and largely restricted to Alveolates, and sedimentation analysis supports the idea that they form a large complex. Analysis of three other members of this putative complex, called MDD (for Mucocyst Docking and Discharge), shows that they also localize to mucocysts. Negative staining of purified MDD complexes revealed distinct particles with a central channel. Our results uncover a novel macromolecular complex whose subunits are conserved within alveolates but not in other lineages, that is essential for regulated exocytosis in T. thermophila.
Keywords: Exocytosis; organely; Tetrahymena; exocytóza; lyzozomy; Tetrahymena thermophila; Animals; Organelles; Secretory Vesicles; sekreční vezikuly; Lysosomes; zvířata